If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -8) = 5(2x + 8) Reorder the terms: 3(-8 + 2x) = 5(2x + 8) (-8 * 3 + 2x * 3) = 5(2x + 8) (-24 + 6x) = 5(2x + 8) Reorder the terms: -24 + 6x = 5(8 + 2x) -24 + 6x = (8 * 5 + 2x * 5) -24 + 6x = (40 + 10x) Solving -24 + 6x = 40 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -24 + 6x + -10x = 40 + 10x + -10x Combine like terms: 6x + -10x = -4x -24 + -4x = 40 + 10x + -10x Combine like terms: 10x + -10x = 0 -24 + -4x = 40 + 0 -24 + -4x = 40 Add '24' to each side of the equation. -24 + 24 + -4x = 40 + 24 Combine like terms: -24 + 24 = 0 0 + -4x = 40 + 24 -4x = 40 + 24 Combine like terms: 40 + 24 = 64 -4x = 64 Divide each side by '-4'. x = -16 Simplifying x = -16
| -14-2k=-8-5(-8+5k) | | 16=8+(-a) | | 0.15y+0.08(y+4000)=1240 | | f(x)=2.45x^2-6.13x-3.68 | | 6-5(2x+3)=11 | | 2(x+4)+7x=3(x+4) | | 6(x-3)+2x-5=27 | | 2x+4+3(2x+2)=34 | | h=2.5433(7.5)+28.465 | | 4x+3x+9=2(x+8) | | 9x+2=7x+3x-5 | | 2m-3-3m=20-m | | 8M-4M-6-3+5M=56-1 | | 2x^3-18x=2x(x-3)(x+3) | | 5x+9+2x+7=2x+11 | | 7.5=3.2-2.1 | | -28+s=11 | | 6+2(x+4)=3(x+5) | | 1.5x-3.5=-.5 | | 2/3x-7/2=-1/2 | | 3/2x7/2=-1/2 | | 15=-5+zx-18 | | 37=.0021x^2-.286x+16.28 | | 3x+2y-z=9 | | 9=(x-41)/18 | | X+5+(-5)=11 | | -9y+7=25y-4 | | 3(6z-1)-4(z+5)=6(z+1) | | 3(r-6)+2=4(r+2) | | 17x-36=3x+6 | | X-100=Y | | 32+.75=47 |